Data engineering for sustainable agriculture: developments, challenges, and case studies of a novel IoRT architecture - Bimonte, Sandro; Bellocchi, Gianni; Pinet, François; Chalhoub, Gérard; Sakr, Mahmoud; Skrzypczyński, Piotr (Journal of big data, 2025)
In recent years, the integration of Internet of Things (IoT) and Robotics has advanced agro-ecological practices. Despite numerous solutions for specific farming applications, a comprehensive reference architecture that addresses the diverse data management and operational requirements of agro-ecology remains absent. This paper introduces a concept of novel architecture for an Internet of Robotic Things (IoRT) system designed to manage the voluminous, real-time, and heterogeneous data in agricultural applications. By leveraging existing frameworks and technologies, this architecture aims to provide robust data management, ensure data quality, and support sustainable farming practices. The proposed architecture is demonstrated through case studies, which show its applicability and efficiency in real-world scenarios. This work is aimed at providing a guideline for researchers and engineers in developing and implementing smart farming solutions with Big Data, IoT and Robotics.